BIBO stabilisation of continuous-time Takagi?Sugeno systems under persistent perturbations and input saturation - Salcedo, José V.; Martínez, Miguél; García-Nieto, Sergio; Hilario, Adolfo (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a novel approach to the design of fuzzy state feedback controllers for continuous-time non-linear systems with input saturation under persistent perturbations. It is assumed that all the states of the Takagi-Sugeno (TS) fuzzy model representing a non-linear system are measurable. Such controllers achieve bounded input bounded output (BIBO) stabilisation in closed loop based on the computation of inescapable ellipsoids. These ellipsoids are computed with linear matrix inequalities (LMIs) that guarantee stabilisation with input saturation and persistent perturbations.
Keywords: LMIs; fuzzy systems; non-linear systems; input saturation; disturbances